APLIKASI KINCIR MINI PADA BUDIDAYA UDANG GALAH (Macrobrachium rosenbergii) SKALA RUMAH TANGGA - Indra Kristiana; Igfirlii Amatullah; Atiek Pietoyo; DH Guntur Prabowo; Dinno Sudinno (Jurusan Akuakultur, Universitas Bangka Belitung, 2021)
Giant freshwater prawns, one of the freshwater aquaculture commodities which has high economic value and has wide market opportunity. Dissolved oxygen on giant freshwater prawn aquaculture is the one of necessary part on a prawn weight gain. Availability of dissolved oxygen can be increased by optimalization on mini wheel and blower use. Mini Wheel is a part of aquaculture technology application, especially on household scale aquaculture of giant freshwater prawn (M. rosenbergii). This assembly used recycle material which can still be used. This mini wheel was modified by 3 treatments, that A (blower without mini wheel pond treatment); B (one-propeller mini wheel pond treatment); C (two-propeller mini wheel pond treatment). This research used quantitative method and every treatment should has three repetitions. Aquaculture a household scale by applying mini wheel designed to find out its effect on water quality and growth of giant freshwater prawn (M. rosenbergii), with parameter ABW (Average Body Weight), ADG (Average Daily Growth), FCR (Feed Convertion Ratio) and SR (Survival Rate). This research showed that there is a significant difference between two-propeller mini wheel pond treatment, one-propeller mini wheel pond treatment and blower without mini wheel pond treatment. The optimum Dissolved Oxygen value on two-propeller mini wheel pond treatment was about 9 mg/L (morning and afternoon testing), Pond temperature on range 280C, and also pH has stability on 7. The best growth was found in two-propeller mini wheel pond treatment with Survival Rate (SR) 93%, Average Body Weight (ABW) 10 g/prawn, Average Daily Growth (ADG) 0.11 g/prawn, and Feed Convertion Ratio (FCR) 1.5.